A safe teaching protocol of LRP (Laparoscopic Radical Prostatectomy) - Tobias-Machado, Marcos; Pazeto, Cristiano Linck; Neves-Neto, Oseas Castro; Nunes-Silva, Igor; Zampolli, Hamilton de Campos (International Brazilian Journal of Urology, 2018)
The LRP has a steep learning curve to obtain proficiency during which patient safety may be compromised. We present an adapted modular training system which purpose to optimize the learning curve and perform a safe surgery. A retrospective analysis of the LRP safe learning protocol applied during a fellowship program over eight years (2008-2015). The surgery was divided in 12 steps and 5 levels of difficulty. A maximum time interval was stipulated in 240 minutes. After an adaptation, the fellows had 120 minutes to perform all the corresponding modules to its accumulated skill. The participants gradually and safely pass through the steps and difficulty levels. Surgeries performed by fellows were analyzed as a single group and compared to a prior series performed by tutor. In eight years, 250 LRP were performed (25 per apprentice) during fellowship program and 150 procedures after completion. The baseline characteristics were comparable. Most cases operated were of intermediate risk. Mean operative time was longer in the fellow group when compared to the tutor (150 min). Mean estimated blood loss were similar among the groups. Functional and oncological outcomes were better in the Tutor´s group. No conversion to open surgery was performed. The LRP safe learning protocol proved to be an effective method to optimize the learning curve and perform safe surgery. However, the tutor's functional and oncological results were better, showing that this is a procedure with a steep learning curve and proficiency demands more than 25 cases.